Comparison of count-based multimorbidity measures in predicting emergency admission and functional decline in older community-dwelling adults: a prospective cohort study. Issue 9 (20th September 2016) - Wallace, Emma; McDowell, Ronald; Bennett, Kathleen; Fahey, Tom; Smith, Susan M
Abstract : Objectives: Multimorbidity, defined as the presence of 2 or more chronic medical conditions in an individual, is associated with poorer health outcomes. Several multimorbidity measures exist, and the challenge is to decide which to use preferentially in predicting health outcomes. The study objective was to compare the performance of 5 count-based multimorbidity measures in predicting emergency hospital admission and functional decline in older community-dwelling adults attending primary care. Setting: 15 general practices (GPs) in Ireland. Participants: n=862, ≥70 years, community-dwellers followed-up for 2 years (2010–2012). Exposure at baseline : Five multimorbidity measures (disease counts, selected conditions counts, Charlson comorbidity index, RxRisk-V, medication counts) calculated using GP medical record and linked national pharmacy claims data. Primary outcomes: (1) Emergency admission and ambulatory care sensitive (ACS) admission (GP medical record) and (2) functional decline (postal questionnaire). Statistical analysis: Descriptive statistics and measure discrimination (c-statistic, 95% CIs), adjusted for confounders. Results: Median age was 77 years and 53% were women. Prevalent rates ranged from 37% to 91% depending on which measure was used to define multimorbidity. All measures demonstrated poor discrimination for the outcome of emergency admission (c-statistic range: 0.62, 0.65), ACS admission (c-statistic range: 0.63, 0.68) and functional decline (c-statistic range: 0.55, 0.61). Medication-based measures were equivalent to diagnosis-based measures. Conclusions: The choice of measure may have a significant impact on prevalent rates. Five multimorbidity measures demonstrated poor discrimination in predicting emergency admission and functional decline, with medication-based measures equivalent to diagnosis-based measures. Consideration of multimorbidity in isolation is insufficient for predicting these outcomes in community settings.